Human papillomavirus-related multiphenotypic sinonasal carcinoma: First case report associated with an intermediate-risk HPV type and literatures review - Komkrit Ruangritchankul; Tikamporn Jitpasutham; Nakarin Kitkumthorn; Paul Scott Thorner; Somboon Keelawat (Elsevier, 2018)
HPV-related Multiphenotypic sinonasal carcinoma (previously known as HPV-related carcinoma with adenoid cystic carcinoma-like features) is very rare tumor of which only 55 cases are reported. All cases to date are related to high-risk types of HPV including 16, 31, 33, 35 and 56. We report of a case of a nasal mass in a 50-year-old female. Biopsy demonstrated typical features of an HPV-related multiphenotypic sinonasal carcinoma, with both basaloid and ductal type cells. Tumor cells were arranged in lobulated sheets, with focal cribriform and microcystic growth patterns. The majority of tumor cells expressed myoepithelial markers (S-100 protein, smooth muscle actin and p63) and the ductal cells were immunopositive for CD117. Polymerase chain reaction and sequencing identified HPV type 26. HPV 26 becomes the first intermediate risk type that may be associated with HPV-related multiphenotypic sinonasal carcinoma. Keywords: HPV, Type 26, Sinonasal carcinoma, Multiphenotypic